Development of a Gamification-Based Virtual Laboratory Media to Enhance Scientific Thinking Skills of Elementary School Students - Puspitasari, Puspa; Uswatun, Din Azwar; Sutisnawati, Astri (FKIP - Universitas Riau, 2026)
Science learning in elementary schools still faces problems, especially in practical activities that result in low scientific thinking skills. This study aims to develop gamification-based virtual laboratory media as a solution to improve scientific thinking skills in science learning in elementary schools. This study applied a Research and Development (R&D) approach by adapting the Borg & Gall model to evaluate the feasibility and effectiveness of the developed product. The media was designed in a website format that integrated images, materials, visualizations, instructional videos, virtual practical activities, and interactive quizzes. Expert validation results showed that the developed media was feasible for use with a rating in the excellent category. In addition, the effectiveness test results showed an increase in scientific thinking skills based on pretest and posttest scores after using the gamification-based virtual laboratory media. Thus, this study shows that gamification-based virtual laboratory media is feasible to use and effective in improving scientific thinking skills in science learning in elementary schools.